Passive Q-Switching of a Diode-Pumped Pr:LiYF4 Visible Laser Using WS2 as Saturable Absorber - Yongjie Cheng; Jian Peng; Bin Xu; Han Yang; Zhengqian Luo; Huiying Xu; Zhiping Cai; Jian Weng (IEEE Photonics Journal)
Q-switched laser operation of a blue-diode-pumped Pr:LiYF4 laser is demonstrated at 640 nm for the first time by using a tungsten disulfide (WS2) nanosheet material as a saturable absorber. Stable laser pulses of 630 ns are obtained with a pulse repetition rate of 88 kHz, a pulse energy of about 0.24 $μ\text{J}$ , and an average output power of 21.5 mW. This paper broadens the application of WS2-like 2-D nanosheet saturable absorbers from the near- and mid-infrared to the visible domain.